2004
DOI: 10.1038/sj.bmt.1704736
|View full text |Cite
|
Sign up to set email alerts
|

CD8+ T-cell-depleted, matched unrelated donor, allogeneic bone marrow transplantation for advanced AML using busulfan-based preparative regimens

Abstract: Summary:The role of T-cell depletion (TCD) to prevent graftversus-host disease (GVHD) after matched unrelated donor allogeneic bone marrow transplant (MUD BMT) remains undefined. Most studies employ total body irradiation and pan TCD. Between March 1993 and June 2002, we treated 33 relapsed acute myelogenous leukemia (AML) patients with busulfan-based preparative regimens and selective TCD. The preparative regimen consisted of busulfan 14 mg/kg, cyclophosphamide 120 mg/kg and VP-16 50 mg/kg in all but one pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Limited reports of TCD unrelated BM or PBSC grafts following myeloablation have been published7,23-26 Most studies utilized partial TCD together with immune suppressive medications25 post transplant. They reported slower immune recovery, a higher incidence of infectious complications, 18,27,28 and relapse in certain diseases compared with T-cell replete transplantation 29-31.…”
Section: Discussionmentioning
confidence: 99%
“…Limited reports of TCD unrelated BM or PBSC grafts following myeloablation have been published7,23-26 Most studies utilized partial TCD together with immune suppressive medications25 post transplant. They reported slower immune recovery, a higher incidence of infectious complications, 18,27,28 and relapse in certain diseases compared with T-cell replete transplantation 29-31.…”
Section: Discussionmentioning
confidence: 99%
“…CD8+ T cells were more abundant than CD4+ T cells in the blood of mice after aGVHD induction, and the severity of aGVHD was associated with the in ltration of CD8+ T cells in target tissues [44]. Several studies reported that CD8+ T cells count in the graft could predict the aGVHD in patient receiving ISD HSCT [16], URD HSCT [45], and umbilical cord blood transplantation [46].…”
Section: Discussionmentioning
confidence: 99%
“…Depletion of all CD8 þ T cells has also been attempted, based on data supporting their critical role in human GvHD [30][31][32]. The hope is that the spared CD4 þ subset will be sufficient to allow immune recovery.…”
Section: Selective Depletion Of Cd8 R T Cellsmentioning
confidence: 97%